2021
DOI: 10.3390/ijms222312898
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Hypoxia on Cytokine Expression Involved in Insulin Resistance

Abstract: Sleep apnea syndrome (SAS) is a prevalent disorder characterized by recurrent apnea or hypoxia episodes leading to intermittent hypoxia (IH) and arousals during sleep. Currently, the relationship between SAS and metabolic diseases is being actively analyzed, and SAS is considered to be an independent risk factor for the development and progression of insulin resistance/type 2 diabetes (T2DM). Accumulating evidence suggests that the short cycles of decreased oxygen saturation and rapid reoxygenation, a typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 115 publications
1
8
0
Order By: Relevance
“…The results of the present study also suggest that chronic intermittent hypoxia leads to modulation in the glucose metabolism in the DEN-induced rat model. This is in accordance with previously reported studies showing chronic intermittent hypoxia-related alterations in fasting glucose levels and glucose metabolism in general [35][36][37].…”
Section: Discussionsupporting
confidence: 94%
“…The results of the present study also suggest that chronic intermittent hypoxia leads to modulation in the glucose metabolism in the DEN-induced rat model. This is in accordance with previously reported studies showing chronic intermittent hypoxia-related alterations in fasting glucose levels and glucose metabolism in general [35][36][37].…”
Section: Discussionsupporting
confidence: 94%
“…Our cellular studies have indicated that IH, a hallmark manifestation of SAS, is involved in the reduction in glucose-induced insulin secretion by down-regulation of CD38 in pancreatic β cells [ 6 ]; the up-regulation of selenoprotein P and HIP/PAP via down-regulation of miR-203 in hepatocytes [ 5 ]; the up-regulation of adipokines, such as CCL2, TNF-α, and RETN via down-regulation of miR-452 in adipocytes [ 78 ]; and the up-regulation of myokines, such as IL-8, osteonectin, and myonectin, in myocytes [ 79 , 80 , 81 ], all of which can contribute to obesity [ 82 ]. On the other hand, we have also revealed the IH-induced up-regulation of POMC and CART mRNA expression via GATA transcription factors in neuronal cells [ 104 ] and the up-regulation of PYY , GLP-1 , and NTS mRNAs through alteration in the chromatin structures of the PYY , GLP-1 , and NTS genes in enteroendocrine cells [ 106 ], both of which suggest possible anorexigenic effects of IH on the gut–brain axis.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, there is accumulating evidence indicating that IH induces the impairment of glucose tolerance and insulin resistance in pancreatic β cells, hepatocytes, adipocytes, and skeletal muscle cells, which may contribute to obesity [ 82 ] ( Figure 1 ).…”
Section: Ih and Impaired Glucose Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, there is accumulating evidence indicating that IH induces impaired glucose tolerance and insulin resistance in pancreatic β cells, hepatocytes, adipocytes, and skeletal muscle cells by upregulating the genes responsible for insulin resistance [ 69 ] ( Figure 2 ).…”
Section: The Effect Of Ih On Insulin Resistancementioning
confidence: 99%